Heart rate variability biofeedback: implications for cognitive and psychiatric effects in older adults. (4th May 2019) - Jester, Dylan J.; Rozek, Ellen K.; McKelley, Ryan A.
ABSTRACT: Objectives: Two decades of heart rate variability (HRV) biofeedback research have focused on adolescent and adult populations with a variety of symptoms and conditions at the exclusion of older adults. This study explores HRV biofeedback as a novel treatment to decrease psychiatric symptoms and improve cognitive functioning in older adults. Methods: Participants enrolled in a three-week intervention that included six 30-min biofeedback sessions. Neuropsychological and psychiatric measures were administered before and after the intervention. Results: Decreases in depression (Cohen's d = 1.02, p < .001), state anxiety (Cohen's d = 0.82, p = .003), and trait anxiety (Cohen's d = 0.84, p = .002) were observed. An increase in attentional skills as measured by the Trail Making Test – Part A was seen (Cohen's d = 1.00, p = .001). Differences in executive skills as measured by the Trial Making Test – Part B and the Stroop Task did not reach statistical significance. Conclusion: This study suggests that older adults may benefit from HRV biofeedback interventions much like the younger populations that have been studied for decades. Depression, anxiety, and attentional skills were positively affected. Several participants reported improved sleep quality and stress management. Future studies should corroborate these findings.